GINGERS OF LOMBOK - Marlina Ardiyani; Yessi Santika; Jin Hyub Paik; Anshary Maruzy; Axel Dalberg Poulsen (PTTI, 2012)
The ginger flora of the Lesser Sunda islands is very poorly known. A preliminary survey of Lombok in 2011 documented five wild species (Etlingera rubroloba, E. calophrys, Amomum maxium, A. gracile, Alpinia sp. and Globba marantina). The species of Alpinia cannot immediately be identified and may be new. A key to the genera and species is included in this account as well as photographs.